Rhizosphere microorganisms potential antagonists fusarium sp. causing root rot of passion fruit (passiflora edulis sims) (2012)
The passion fruit crop (Passiflora edulis) is very important for the Colombian economy. Nowadays this crop is affected by damping-off disease caused by Fusarium sp. So, it is necessary to look for alternatives which allow us to control the disease efficiently. The bacteria Azotobacter spp., Azoospirillum spp. and the fungi Trichoderma spp., were evaluated as a Fusarium sp. potential biocontrol in In vitro and In vivo test. The research was carried out in laboratory and nursery. The “dual test” showed that a wild isolate of Trichoderma spp. and a commercial product (Trichoderma lignorum), inhibited the mycelial growth of Fusarium sp. between 94.2 and 93.6% respectively. Trichoderma evaluation on passion fruit plantlets at three application times demonstrated that applying Trichoderma before Fusarium sp. appearance, decreased the disease occurrence between 75.0 and 50.0%, whereas applying Trichoderma after or simultaneously with the pathogen, the disease in the plantlets decreased until 25.0%. This suggests that inoculation of pregerminated seeds with bio-control agents improved the protection of plants against the pathogenic and they are an important tool for management of diseases in plants of passion fruit.